PENGARUH MODEL PEMBELAJARAN NOMINAL GROUP TECHNIQUE (NGT) TERHADAP HASIL BELAJAR BIOLOGI - Murnihati Sarumaha (Jurnal Education and Development, 2021)
This research is motivated by the opinion of experts and previous research that there is an influence of the Nominal Group Technique (NGT) learning model on student learning outcomes. Learning is still dominated by teachers due to the use of the lecture learning model. The purpose of the study was to determine whether the Nominal Group Technique (NGT) learning model on students' science learning outcomes. The subjects of this research are students. Based on the calculation of the Hypothesis Test = 2.02 and t table = 1.66 obtained t count> t table then HO and Ha are accepted. The conclusion model is that the Nominal Group Technique has an impact on students in improving learning outcomes, initially students are less active, silent, and lack motivation and interest in learning due to several factors, but because of the implementation of the Nominal Group Technique learning model which has advantages in increasing student activity and creativity. so that learning outcomes increase. The suggestions put forward by the research are (1) teachers and educational practitioners are advised to apply the Nominal Group Technique (NGT) learning model in order to improve the ability to become student learning outcomes and (2) the results of this study can be used as a basis for further research development. continue to be student learning outcomes.